Pharmacokinetic, bioequivalence, and safety assessments of two brands of 30-mg nifedipine controlled-release formulations in Chinese healthy subjects - Lu, Huan; Zhou, Fei; Rui, Cuijie; You, Hen; Zhang, Wenhao; Zhang, Yaxin; Ding, Juefang; Zhao, Shunbo; Wu, Qiang (International journal of clinical pharmacology and therapeutics, 2024)
This study aimed to analyze the pharmacokinetic (PK) characteristics, safety, and bioequivalence (BE) of a test (T) preparation of a nifedipine controlled-release tablet and the reference (R) drug (Adalat GTIS) in Chinese study participants in the context of fasting and postprandial states. An open-label, single-center, randomized, single-dose, two-period study was designed including two separate arms, one with administration under fasting conditions and one with administration under postprandial conditions (high-fat, high-calorie breakfast). After oral administration, the nifedipine concentrations in plasma were quantitatively analyzed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) at regular intervals. Primary PK parameters, including the area under the concentration curve from 0 to infinity (AUC ), the area under the concentration profile from 0 to the last measurable concentration time (AUC ), and maximal measured plasma concentration (C ) were log-transformed with BE limits of 80 - 125% to evaluate BE. All adverse events (AEs) were wholly supervised. The PK profiles of the T and R formulations were comparable to each other under both fasting and postprandial conditions. The 90% confidence intervals (CIs) of the AUC , AUC , and C were 92.69 - 106.06%, 93.32 - 107.05%, and 99.53 - 116.71%, respectively, under the fasting state. The 90% CIs of the AUC , AUC , and C were 105.05 - 117.40%, 105.43 - 117.82%, and 102.66 - 116.30%, respectively, in the postprandial arm. 47 cases of drug-associated AEs were noted in the entire research. Under both the fasting and postprandial states, the two nifedipine controlled-release formulations were bioequivalent and safe in healthy Chinese subjects.